Commonality in Liquidity in the Context of Different Trading Systems: Evidence from an Emerging Market - Tayeh, Mohammad (International Journal of Economics and Financial Issues, 2016)
We offer hitherto unpublished evidence of the impact of different trading systems on commonality in liquidity from an emerging market i.e. The Amman Stock Exchange. We argue that the degree of responsiveness of individual stock’s liquidity to changes in market-wide liquidity will vary before and after the automation of a trading system, due to the differences in market structure. In general, the results show different sensitivities in the stock liquidity to changes in market-wide liquidity on both trading systems; the mean coefficient of concurrent market-wide liquidity on an electronic trading system is larger than that on a floor trading system. We also provide evidence on the existence of size effect in commonality. However, regardless of the size pattern revealed in commonality, the liquidity of firms in electronic trading system shows a stronger response to changes in market-wide liquidity. Finally, the results show the existence of commonality within the same industry, which is also stronger after the automation of a trading system. The above results imply that the floor trading system is less vulnerable to the information asymmetry problem. Keywords: Liquidity, commonality, market microstructure, information asymmetry, floor trading system, electronic trading systems. JEL Classifications: D47; D82; G10; G18